THE INFLUENCE OF THE FAMILY ENVIRONMENT ON STUDENT LEARNING OUTCOMES IN IPS LESSON IN SDN 83 KOTA TENGAH KOTA GORONTALO - ELMIA UMAR; FAUZIAH MAKALUNSENGE (International Journal of Innovations in Engineering Research and Technology, 2021)
Purpose this study was to determine how much influence the family environment has on student learning outcomes in social studies lessons at SDN 83 Kota Tengah Kota Gorontalo. The method used in this research is quantitative method with data collection through observation, questionnaires and documentation using simple regression data analysis. The results showed the students at SDN 83 Kota Tengah Kota Gorontalo, it was concluded that the family environment was one of the factors that had an influence on student learning outcomes. The influence of the contribution of 35.4% to the student learning outcomes variable, while the other 64.6% is influenced by other factors outside the variables studied. So the findings of this study are in accordance with the mindset put forward in the conceptual framework in which a good family environment tends to have a positive effect, so that children’s learning outcomes are good. Conversely, if the family environment is not good, a large trend will have a negative impact on student development